Isotopic branching in (He, HD+) collisions: A time-dependent quantum mechanical study in three dimensions - Kalyanaraman, C; Clary, D; Sathyamurthy, N (1999)
A time-dependent quantum mechanical approach has been used to investigate the reaction He+HD+(v = 0 - 4,j = 0 - 3)→HeH++D; HeD+ + H in three dimensions for total angular momentum J = 0. The vib-rotation (v,j) state-selected reaction probability (PRv,j) is shown to increase with v over the collision energy (Etrans) range (0.95-2.25 eV) investigated for both the exchange channels, in accord with the experimental results. The isotopic branching ratio F = PR(HeH+)/PR(HeD+) generally remains less than unity for different v states at different Etrans in agreement with experiment. But at Etrans= 1.0 eV, for v = 4, F obtained from our calculations for j = 0 of HD+ is ∼0.8, in excellent agreement with the earlier quasiclassical trajectory calculations, but a factor of 2 less than that obtained from experiment. This difference could arise from the inclusion of nonzero j states in the experimental study, as PRv,j is found to be j dependent for both the channels. While PRv,j (HeH+) decreases initially with increase in j from 0 to 2 and then increases when j is increased further to 3, PRv,j (HeD+) reveals an unusual j dependence; it is larger for even j states of HD+ than for odd j. As a result, F is strongly dependent on j, in contrast to the marginal dependence shown by the earlier quasiclassical trajectory calculations. © 1999 American Institute of Physics.